Analisis Manajemen Risiko ISO 31000 Pada Pondok Pesantren Luhur Al-Husna - Tiara Anggraini; Andrian Joko Saputro; Khafila Roudhotul Jannah; Lutfia Sahrani; Tiana Rahmanita Firdaus; Novie Andriani Zakariya (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this study was to analyze ISO 31000 at the Luhur Al-Husna Islamic Boarding School. The research method uses a qualitative approach with data collection techniques conducting interviews and observations. Risk management consists of risk identification, risk analysis, risk adjustment and risk treatment. The results showed that the Luhur Al-Husna Islamic Boarding School had risks related to the operational activities of the cottage. These risks have not been fully managed properly so that they can hinder future cottage activities. The results of the risk evaluation identified 2 extreme risks at the Luhur Al-Husna Islamic Boarding School, namely problems with skipping students and students who are in arrears in payments. The treatment given to extreme risks includes forming a discipline division and giving reprimands and time limits. Categorized by several indices, namely extreme, medium low and very low.